Analysis of Key Characteristic Components of Nitraria tangutorum Bobrov and Black Wolfberry Berries Based on Non-targeted Metabolomics - CHEN Hao, CHI Ming, LI Ying, ZHANG Yanzhen, SHAN Bin, WANG Yuze, ZHANG Yulin, WANG Xuefei, XI Zhumei (Shipin Kexue)
The characteristic metabolic components of two specialty wild berries in the Qaidam Basin, northwest China (Nitraria tangutorum Bobrov and the black wolfberry Lycium ruthenicum Murr) were explored. Their non-volatile and volatile substances were identified and screened using ultra-high performance liquid chromatography-quadrupole time-of-flight mass spectrometry (UPLC-QTOF-MS), gas chromatography-ion mobility spectrometry (GC-IMS) and gas chromatography-mass spectrometry (GC-MS). The results showed that the reducing sugar content of N. tangutorum Bobrov was 196.46 g/L, which was significantly higher than that of black wolfberry. The titratable acid content of N. tangutorum Bobrov was 3.43 g/L, and the total phenol content was 7.03 mg/g, which was significantly lower than that of black wolfberry. The major monomeric phenolic compounds in both berries were flavonoids. The characteristic monomeric phenolics in N. tangutorum Bobrov were albiflorin, dicoumarin and paeoniflorin, while those in black wolfberry were naringin, phlorizin, and proanthocyanidin B1. The characteristic volatile substances in N. tangutorum Bobrov were isononanoic acid, farnesene, ethyl 3-methylbutyrate, (-)-4-terpineol, nonanal, ethyl hexanoate and L-rose oxide, and its fruity, floral and cheese-like aroma characteristics were prominent. The characteristic volatile substances of black wolfberry were methyl octanoate, 1-octen-3-ol, (E)-3-hexen-1-ol, (Z)-3-hexen-1-ol, decanal, nerol, citronellol, D-limonene, and its flowery, fruity, grassy, mushroom-like and earthy aroma characteristics were prominent. After screening, identification and statistical analysis, the top ten most significantly differential non-volatile compounds between the two berries were found to be histidine, myricetin-3-glucoside, proline, iridone-4’-glucoside, 2,3-dihydroxybenzoic acid, isovalerylglutamic acid, caffeic acid, 3-hydroxyphenylacetic acid, isorhamnetin-3-glucoside and peoniflorin-3-O-glucoside. The results of this study can provide a theoretical basis for the development and utilization of differentiated high-value products from N. tangutorum Bobrov and black wolfberry.